2016
DOI: 10.1194/jlr.d064618
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed peptide analysis for kinetic measurements of major human apolipoproteins by LC/MS/MS

Abstract: those of the entire lipoprotein metabolism ( 1, 3 ). The incorporation of a labeled amino acid into the protein during its synthesis is subsequently measured over time and analyzed with a compartmental model to obtain the kinetic data ( 4, 5 ). The reference method to measure tracer enrichments involves isolation of the Apos by gel electrophoresis followed by acid hydrolysis to obtain unlabeled and labeled amino acids. Then, the amino acids are derivatized for GC/ MS analysis ( 3 ). These approaches are limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…Lipoprotein turnover can be assessed in vivo by measuring the incorporation of an injected tracer, usually 2 H 3 -leucine, in apolipoproteins over time, allowing the determination of lipoprotein kinetic parameters such as their production rates (PRs) and fractional catabolic rates (FCRs) (9). This approach has been improved by new analytical techniques involving enzymatic proteolysis and LC-MS/MS (10,11). LC-MS/MS is a powerful tool to simultaneously quantify several plasma proteins even at low concentrations (12,13).…”
Section: Kinetics Of Plasma Apoe Isoforms 893mentioning
confidence: 99%
See 2 more Smart Citations
“…Lipoprotein turnover can be assessed in vivo by measuring the incorporation of an injected tracer, usually 2 H 3 -leucine, in apolipoproteins over time, allowing the determination of lipoprotein kinetic parameters such as their production rates (PRs) and fractional catabolic rates (FCRs) (9). This approach has been improved by new analytical techniques involving enzymatic proteolysis and LC-MS/MS (10,11). LC-MS/MS is a powerful tool to simultaneously quantify several plasma proteins even at low concentrations (12,13).…”
Section: Kinetics Of Plasma Apoe Isoforms 893mentioning
confidence: 99%
“…Apolipoproteins (apoA-I, apoB100, apoC-II, apoC-III, and apoE) were analyzed in plasma, lipoprotein fractions, and concentrated lipoprotein fractions using a validated multiplexed assay involving trypsin proteolysis and the subsequent analysis of proteotypic peptides by LC-MS/MS (10). The method was updated for the quantification of apoE isoforms as described previously (2).…”
Section: Sample Preparation and Proteolytic Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…4a). In the last few years the metabolism of proteins such as apo(a), apoB, PCSK9, and CETP isolated from plasma or VLDL/LDL [27, 34, 54, 63, 64], or a subset of the classical apolipoproteins from HDL [52] have been studied in humans using MRM on the triple quadrupole platform (Fig. 4a).…”
Section: Targeted Proteomics Applied To Hdl Biologymentioning
confidence: 99%
“…As a consequence of this detection constraint, most apolipoprotein metabolism studies have been limited to either the quickly turning over apoB (~10% enrichment) or to the total HDL plasma pool (up to 2% peak enrichment depending on the labeling strategy). 68 Singh et al from our laboratory, however, demonstrated the ability of PRM to measure <1% tracer enrichment in not only apoA-I from 5 HDL size fractions, but also 6 additional HDL apolipoproteins. 72 Figure 7B demonstrates a PRM scan of the apoA-I peptide, THLAPYSDELR.…”
Section: Selected Reaction Monitoring (Srm) and Parallel Reaction Monmentioning
confidence: 99%